Development of an Infectious Cell Culture System for Hepatitis C Virus Genotype 6a Clinical Isolate Using a Novel Strategy and Its Sensitivity to Direct-Acting Antivirals - Chen, Mingxiao; Zheng, Fuxiang; Yuan, Guosheng; Duan, Xiaobing; Rong, Liang; Liu, Junwei; Feng, Shengjun; Wang, Ziting; Wang, Min; Feng, Yetong; Zhou, Qing; Li, Jinqian; et al. (Frontiers in Microbiology, 2018)
Hepatitis C virus (HCV) infection is a leading cause of hepatoma worldwide. HCV is classified into seven major genotypes, and genotype 6 is commonly prevalent in Asia. An efficient infectious culture system representative of genotype 6 isolates that are currently prevalent is important for HCV research. Here, we developed robust infectious cell culture system for genotype 6a clinical isolate CH6a using a novel strategy. Initially, we determined a consensus CH6a sequence using patient serum, and assembled CH6a full-length recombinant using the overlapped PCR-derived clones that shared high homology with the consensus sequence. However, CH6a full-length was non-infectious in hepatoma Huh7.5 cells. Next, we constructed JFH1-based CH6a Core-NS5A and 5’UTR-NS5A recombinants with mutations identified previously and found that 7 mutations promoted low level of replication but no virus spread. The 7 mutations, in combination with mutations found in infectious CH6a Core-NS2 recombinant, could adapt Core-NS5A recombinant. Combination of 22 mutations identified previously and in this study promoted the replication of CH6a ORF recombinant (CH6aORF_22m) with JFH1-5’UTR/3’UTR. Finally, we generated CH6aORF_26m and CH6a_26m (designated “CH6acc”) recombinants, and both viruses replicated efficiently in Huh7.5.1-VISI-mCherry and Huh7.5 cells, releasing infectivity titers of 104.3-104.5 focus-forming units (FFU)/ml. The engineered mutations were maintained without acquirement of additional mutations after viral passages. The CH6a virus was inhibited by direct-acting antivirals simeprevir and sofosbuvir in a dose-dependent manner. The CH6acc permits the studies of this important HCV genotype, and the strategy using a consensus-like clone and mutations will facilitate culture development of other HCV isolates and related viruses.